PENGGABUNGAN GANTI RUGI DALAM PERKARA PERDATA MENURUT SISTEM PERADILAN PIDANA INDONESIA - Adriani Adnani (Ensiklopedia of Journal, 2020)
Compensation in jurisdiction system acts crime of cause facet be divided as 2 kinds which is replacing which because of enforcer fault sentence and because of compensation suspect or defendant. Because of compensation law enforcer was determined deep legislation regulation. Meanwhile for compensation which caused by suspect or defendant is divided up two kinds. To disadvantages material can couple with pidana’s matter but for tuntutkan disadvantages immaterial proposed by ala separates from pidana’s matter.